Five Tensions in the Implementation of the Institutional Improvement Route in Santander, Colombia - Torres-Jaimes, Héctor J. (2023)
This article presents the results of a qualitative study that identifies five tensions experienced by the teaching directors in the implementation of the Institutional Improvement Route (RMI) in official schools of preschool, basic and secondary education in the department of Santander, Colombia. The methodology is qualitative with a social phenomenological approach. A focus group made up of 15 teaching directors was formed, who, in ten virtual work sessions, identified the following five main tensions: First, between the difficulty of balancing administrative processes and pedagogical ones; second, between managerial and pedagogical discourse; third, between the general guidelines derived from regulations and school autonomy; fourth, between the central level objectives in educational matters and the particularities of school institutions; finally, between technical guidelines and institutional culture. These tensions represent complex challenges for the leadership and management of teaching directors in their work towards the institutional improvement. Additionally, they show the need to redefine the management model of the RMI so that it better adjusts to the regional educational context, considers school autonomy, and recognizes the cultural characteristics of educational communities.